The Effect of Price and Content Marketing on Purchasing Decision through Purchase Interest - Sari, Arini Kurnia; Djawoto, Djawoto; Suhermin, Suhermin (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2025)
The development of social commerce has grown in Indonesia since there has been an increase in Gross Merchandise Value. Moreover, trade through social media gives a new interactive experience, thus it becomes a huge potency. This study aimed to examine and analyze the effect of price and content marketing on purchasing interest of TikTok in Surabaya. The population was users of TikTok who had purchasing decisions and were 17-40 years old in Surabaya. Furthermore, the amount number was infinite. Furthermore, the data collection technique used purposive sampling with 110 respondents. The study was descriptive-quantitative and statistic-inferential. Additionally, the data analysis technique used SmartPls. As a result, it concluded that both price and content marketing had a positive and significant effect on purchasing interest. However, the price had a positive but insignificant effect on purchasing decisions. In contrast, content marketing had a positive and significant effect on purchasing decisions. In addition, price, as well as content marketing, had a positive and significant effect on purchasing decisions through purchasing interest of TikTok in Surabaya.